POLICY SCENARIOS FOR SUSTAINABLE URBAN COASTAL DEVELOPMENT: A TECHNOLOGICAL APPROACH IN LABUAN BAJO, INDONESIA - Suharyanto Suharyanto; Akhmad Fauzi; Luky Adrianto; Yudi Wahyudin; Chaterina Agusta Paulus; Xue Xiongzhi; Wan Izatul Asma (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2025)
Aim: to select sustainable coastal city management policies that have the best chance of success. Methodology and results: First, identify problems based on 31 previous research results. The results are problems in Labuan Bajo city management. Second, discuss the problems in FGD stakeholders and experts. The results of the FGD are 61 variables in sustainable coastal cities management, consisting of 11 socio-cultural variables, 17 economic variables, 7 environmental variables, and 25 governance variables. Third, analyzing the reciprocal influence relationship between 61 sustainability variables using the MICMAC technological approach. The results are 21 key variables, 13 critical variables, 23 output variables, and 4 inert variables. Fourth, determine hypotheses/policies and their probabilities through FGD stakeholders and experts. The results are 6 hypotheses/policies and their probability values. Fifth, analyzing 64 alternative scenarios (policy combinations) using the SMIC-Prob technological approach. The results of the analysis are scenarios, their probabilities, and degrees of elasticity. Conclusion, significance and impact study: The highest probability is 12.2%, namely scenario of 111011 (combination of all policies except the 4th policy, namely the policy of "Local workforce capacity development and expansion of employment opportunities/P4).: A technological approach to multi-criteria analysis significantly facilitates urban and environmental planners in finding solutions to the complex problems involved in decision-making regarding sustainable coastal urban development policy scenarios. This approach ensures a transparent and participatory policy planning process, ensuring that the resulting policies meet the interests of all stakeholders.